Development, Implementation, And Application Of E-Areas Of E-Commerce In Malaysia Is A Growing Market (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The fact that the Internet is now so prevalent in corporate usage has driven companies to a number of creative approaches that go far beyond just online marketing and leads to the use of new techniques to success. With the growing number of companies using the internet to perform their activities, consumers would have more choices in terms of where to look for products and services. Today, trading through the internet is expanding in many parts of the world. The growth of this development has been crucial in pushing the country's economy into a more positive state, and is likely to produce a more than adequate income. While the development of Information and Communication Technology (ICT), particularly the Internet, has enabled the general public to take advantage of e-commerce in their daily activities, many businesses now use it to conduct business in Malaysia. E-commerce is commonly used by industry, government, but government alone cannot be seen as the exclusive use. For this reason, the expand-commerce business really gains a great number of advantages to the online customers in the process of everyday work that involves finances. A lot has been written in this article about the use of e-commerce and how it has developed in the recent years in places like Malaysia. In addition, the author looks at the processes and obstacles which have been faced as well as how they were employed to ensure that e-commerce could be an effective in work activities